Biological detail and graph structure in network neuroscience - Papo, David; Buldú, Javier M. (Frontiers in Network Physiology, 2025)
Representing the brain as a complex network typically involves approximations of both biological detail and network structure. Here, we discuss the sort of biological detail that may improve network models of brain activity and, conversely, how standard network structure may be refined to more directly address additional neural properties. It is argued that generalised structures face the same fundamental issues related to intrinsicality, universality and functional meaningfulness of standard network models. Ultimately finding the appropriate level of biological and network detail will require understanding how given network structure can perform specific functions, but also a better characterisation of neurophysiological stylised facts and of the structure-dynamics-function relationship.